Plano estratégico de endomarketing para a empresa Dix - diagnóstico por imagem em Santa Maria - Wachholz, Kymberli Stela (2021)
This experimental project presents a study and strategic planning on endomarketing in healthcare companies, and endomarketing strategies that can contribute to the daily life of DIX - Diagnostic Imaging. The research starts from the importance of using strategies aimed at the internal public of organizations in order to retain the internal customer. Its main objective is the elaboration of a strategic endomarketing planning for the company DIX - Diagnostic by Image. Through the theoretical review, informal conversations and data collection at the study site, it was possible to draw an overview of the current situation in the health area in relation to its daily life and the pandemic situation of Covid-19. Internal marketing, which is increasingly present in companies, becomes essential in all administrative processes, through the use of tools and the realization of strategic actions that retain the internal public and consequently achieve greater performance and engagement.